Ristocetin and Botrocetin Involve Two Distinct Domains of von Willebrand Factor for Binding to Platelet Membrane Glycoprotein lb - Girma, J P; Takahashi, Y; Yoshioka, A; Diaz, J; Meyer, D (Thrombosis and Haemostasis, 1990)
We have evidence that ristocetin and botrocetin mediate binding of von Willebrand Factor (vWF) to platelet glycoprotein lb (GPIb) through two distinct domains on the vWF molecule. This was established by using monoclonal antibodies (MAbs) to vWF and synthetic peptides derived from the sequence of vWF. MAb 322 and MAb NMC/vW 4 both recognize native vWF as well as fragments containing the GPIb-binding domain of vWF, obtained with the following enzymes: trypsin (116 kDa), V-8 pro tease (Spill, 320 kDa) and V-8 protease plus subtilisin (33-28 kDa). Nevertheless, the lack of reciprocal displacement between the two MAbs in experiments of competitive inhibition for binding to vWF demonstrate that their respective epitopes are separate. Both MAbs inhibit 125I-vWF binding to platelet membrane GPIb and vWF-dependent platelet agglutination induced by ristocetin. However, only MAb NMC/vW4 inhibits these functions in the presence of botrocetin and when ristocetin-induced platelet agglutination is inhibited by MAb 322, botrocetin is still able to restore the agglutination. The involvement of two distinct domains of vWF for binding to GPIb in the presence of ristocetin or botrocetin was confirmed in experiments of binding of 125I-vWF to platelets using as competitor synthetic peptides corresponding to the GPIb binding domain of vWF (Cys 474 to Pro 488 and Ser 692 to Pro 708). At a final concentration of 2.5 mM both peptides inhibit more than 90% of the binding of vWF to ristocetin-treated platelets but are unable to modify this binding in the presence of botrocetin. In conclusion our data suggest that botrocetin and ristocetin involve distinct sites on vWF for binding to GPIb.